Results from the WHO external quality assessment for the respiratory syncytial virus pilot, 2016-17 - Sandra Jackson; Teresa C T Peret; Thedi T Ziegler; Natalie J Thornburg; Terry Besselaar; Shobha Broor; Ian Barr; Elsa Baumeister; Mandeep Chadha; Malinee Chittaganpitch; Badarch Darmaa; Joanna Ellis; et al. (United Kingdom, 2022)
Background: External quality assessments (EQAs) for the molecular detection of respiratory syncytial virus (RSV) are necessary to ensure the provision of reliable and accurate results. One of the objectives of the pilot of the World Health Organization (WHO) Global RSV Surveillance, 2016-2017, was to evaluate and standardize RSV molecular tests used by participating countries. This paper describes the first WHO RSV EQA for the molecular detection of RSV.
Methods: The WHO implemented the pilot of Global RSV Surveillance based on the WHO Global Influenza Surveillance and Response System (GISRS) from 2016 to 2018 in 14 countries. To ensure standardization of tests, 13 participating laboratories were required to complete a 12 panel RSV EQA prepared and distributed by the Centers for Disease Control and Prevention (CDC), USA. The 14th laboratory joined the pilot late and participated in a separate EQA. Laboratories evaluated a RSV rRT-PCR assay developed by CDC and compared where applicable, other Laboratory Developed Tests (LDTs) or commercial assays already in use at their laboratories.
Results: Laboratories performed well using the CDC RSV rRT-PCR in comparison with LDTs and commercial assays. Using the CDC assay, 11 of 13 laboratories reported correct results. Two laboratories each reported one false-positive finding. Of the laboratories using LDTs or commercial assays, results as assessed by Ct values were 100% correct for 1/5 (20%). With corrective actions, all laboratories achieved satisfactory outputs.
Conclusions: These findings indicate that reliable results can be expected from this pilot. Continued participation in EQAs for the molecular detection of RSV is recommended.